What is the impact of the teaching Algebraic Expressions and Equations topic with concept cartoons on the students' logical thinking abilities? - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2010)
The purpose of this research is to investigate whether teaching Algebraic Expressions and Equations topic with concept cartoons has impact on students' logical thinking abilities. The research is quasi-experimental study and it was conducted with 92 students in the 7(th) grade in a primary school in Istanbul in 2008-2009 academic years. One experimental group and one control group were used. While the topic Algebraic Expressions and Equations was instructed through from textbook in the control group, it was instructed with concept cartoons in the experimental group. The data gathered through The Logical Thinking Test used before and after the research were assessed through statistical analysis method. While there is a meaningful difference in the pre- and post-tests of the experimental group and control group supporting post-tests in the end of the study, there is no statistically meaningful difference between the post-tests of the groups. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Mathematics education; concept cartoons; algebraic expressions and equations; logical thinking; conceptional learning